PERKALIAN BINER BILANGAN N DIGIT DENGAN 3, 4, 5 DAN 6 - Sriwasito, Putut (MATEMATIKA, 2008)
In this paper we discuss about binary multiplication of n digits number with numbers 3, 4, 5 and 6. To dispose of carry in and carry out in union result table of summation and table of multiplication, those operation are related to Â half of k. Â